New Data on the Poorly Known Jurassic Record of the Turtle Hylaeochelys (Thalassochelydia), Based on New Finds from Portugal - Adán Pérez-García; Bruno Camilo; Francisco Ortega (Diversity, 2023)
Hylaeochelys is the only thalassochelydian turtle identified in the Cretaceous record. A single Lower Cretaceous species is known, Hylaeochelys belli, identified in United Kingdom and Germany and defined in the first half of the 19th century. Less than a decade ago, the presence of Hylaeochelys in the Upper Jurassic was recognized through the find of a single partial shell from West-Central Portugal. It was attributed to a new species, Hylaeochelys kappa. Until now, no other Hylaeochelys specimen was known for either the Iberian Peninsula or the Jurassic record. Two new specimens attributable to Hylaeochelys, from two different Upper Jurassic outcrops of west-central Portugal, are presented here. Its systematic attribution is analyzed. Consequently, knowledge about the anatomy and intraspecific variability of Hylaeochelys kappa is increased.